Nomination - Greek Graphic Design & Illustration Awards (EVGE) - Mouzouropoulos, Theseas (My University, 2026)
The Greek Graphic Design & Illustration Awards (EVGE) nominated the "OVAL" Signage & Wayfinding Design in the category "Signage".
Keywords: Arts and entertainment